Sebuah Aplikasi SMS Gateway Berbasis Web Untuk Penyampaian Informasi (Studi Kasus: Sekolah Dasar Negeri Barengan Boyolali): Aplikasi SMS Gateway Berbasis Web Untuk Penyampaian Informasi (Studi Kasus: Sekolah Dasar Negeri Barengan Boyolali) - Wahyu Nurjali; Ina Sholihah Widiati; Sri Widiyanti (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2023)
The development of education and the delivery of information is increasingly rapid by utilizing increasingly sophisticated technology. One of them is the use of smartphones which are everywhere. However, not all users have the same reasons because of the sophistication of technology. Like the situation of parents and guardians of students at Barengan Boyolali State Elementary School. Parents of students are comfortable and feel that it is enough to just have a cellphone for calls and SMS because the price of a smartphone and maintenance costs can be said to be expensive due to unfavorable economic conditions and areas where the internet does not reach them. Parents of students are also not familiar with the systems available on smartphones such as WA chat, Telegram and other information providers. This makes it increasingly difficult for schools and committees to communicate and convey information to students' parents. So, given the conditions of parents and guardians of students, using a web-based SMS Gateway with gammu is the right solution. This research was conducted to facilitate the delivery of real-time school information by analyzing problem data using the pieces method, forming an application design using the waterfall method as a research flow to meet needs so that the web-based SMS Gateway application with gammu is successful in reducing missed information and it is hoped that parents of students will follow up. quickly and precisely.